2006
DOI: 10.1128/jb.00543-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA Replication and Repair in Thymineless Death in Escherichia coli

Abstract: Inhibition of DNA replication with hydroxyurea during thymine starvation of Escherichia coli shows that active DNA synthesis is not required for thymineless death (TLD). Hydroxyurea experiments and thymine starvation of lexA3 and uvrA DNA repair mutants rule out unbalanced growth, the SOS response, and nucleotide excision repair as explanations for TLD.Thymineless death (TLD), the phenomenon in which exponentially growing cells starved for thymine lose viability, has been researched for over five decades, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
45
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 17 publications
3
45
1
Order By: Relevance
“…4). Recently, Morganroth and Hanawalt have observed that TLD occurs after Hu addition (21). According to our proposal, a recovery of TLD could be expected after Hu addition, but it has to be pointed out that our prediction would be only in the case that the stalled fork underwent RFR under these conditions.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…4). Recently, Morganroth and Hanawalt have observed that TLD occurs after Hu addition (21). According to our proposal, a recovery of TLD could be expected after Hu addition, but it has to be pointed out that our prediction would be only in the case that the stalled fork underwent RFR under these conditions.…”
mentioning
confidence: 52%
“…That these DSBs occurred at or near the replication forks would explain the connection between replication forks stalled by thymine starvation and TLD proposed by Maaloe and Hanawalt in the 1960s after showing that only those cells actively replicating DNA when thymine was removed underwent TLD (13,17). Our proposal is that this connection is not by the replication process itself, as it has been shown not to be required (21), but through the fate of the stalled replication forks when thymine is removed.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…mazEF has been shown to be responsible for programmed cell death under a wide variety of seemingly unrelated stressful conditions (e.g., short-term antibiotic treatments, high temperature, and oxidative shock) by the group of Engelberg-Kulka (14,18,31). However, chromosomally encoded TA system-dependent programmed cell death was not observed in work by other groups (5,7,22,25,26,33,34) and was recently ruled out by our group (38). The other mainstream hypothesis is that amino acid starvation induces chromosomally encoded TA system-dependent bacteriostasis.…”
mentioning
confidence: 72%
“…The nmDNA was characterized as having single-stranded tails or gaps and branching with single-stranded arms. TLD has been related to DNA replication ; nevertheless, ongoing replication does not appear to be required for TLD as same lethality is observed under thymine starvation in the presence of hidroxyurea (Morganroth & Hanawalt, 2006), an inhibitor of the DNA synthesis. By contrast, TLD is suppressed by the addition of rifampicin or cloramphenicol, both inhibitors of the new initiation events of the E. coli chromosomal DNA (Hanawalt, 1963).…”
Section: Reinitiation Events Under Thymine Starvationmentioning
confidence: 93%